Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 8 - Polynomials and Factoring - 8-4 Multiplying Special Cases - Practice and Problem-Solving Exercises - Page 496: 38



Work Step by Step

To simplify the product $(4s-t)^{2}$ we'll apply the rule that states that $(a-b)^{2}$=$a^{2}$-2ab+$b^{2}$ and set a=4s and b=t Therefore, $(4s-t)^{2}$ =$(4s)^{2}$-2(4s)(t)+$(t)^{2}$ =$16s^{2}$-8st+$t^{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.